Wetting transition at a threshold surfactant concentration of evaporating sessile droplets on a patterned surface - Zhong, Xin (2021)
Wetting transitions induced by varying the components in a solution of a drying droplet can lead to its evolving shape on a textured surface. It can provide new insights on liquid pattern control through manipulating droplet solutions. We show the pronounced transitions of wetting for surfactant solution droplets drying on a micropyramid-patterned surface. At low initial surfactant concentrations, the droplet maintains an octagonal shape until the end of drying. At intermediate initial surfactant concentrations, the early octagon spreads to a square, which later evolves to a stretched rectangle. At high initial surfactant concentrations, the droplet mainly exhibits the "octagon-to-square" transition, and the square shape is maintained until the end. The octagon-to-square transition occurs at similar temporal volume-averaged surfactant concentrations for the various initial surfactant concentrations. It results from the dependence of the surface energy change of spread over the micropyramid structure on the temporal volume-averaged surfactant concentration. At high initial surfactant concentrations, the accumulation of the surfactant near the contact line driven by outward flows could raise the local viscosity and enhance the pinning effect, leading to the great suppression of the "square-to-rectangle" transition.